2018
DOI: 10.1002/jeab.469
|View full text |Cite
|
Sign up to set email alerts
|

The effects of outcome unit framing on delay discounting

Abstract: We examined the effects of outcome framing on delay discounting. In Experiment 1, participants completed four delay-discounting tasks. In one monetary task, money was framed in units of dollars ($50), and in the other, money was framed in units of handfuls of quarters (equal to $50). In one food task, food was framed in clear units of food (e.g., 100 M&Ms), and in the other, food was framed in units of servings (e.g., 10 servings of M&Ms). When money was framed in units of dollars, participants discounted less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 65 publications
2
16
1
2
Order By: Relevance
“…We found that choice of the larger amount of money at no delay was affected by framing. These data were reported in summary form in DeHart et al () but not formally analyzed. Here, we report that the proportion of choices for larger clear‐framed money (dollars) at no delay was greater than the proportion of choices for larger fuzzy‐framed money (handfuls of quarters) at no delay (Number of choices of Small Clear Money = 2, Large Clear Money = 238; Small Fuzzy Money = 24, Large Fuzzy Money = 216; z = 4.44, p < .001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that choice of the larger amount of money at no delay was affected by framing. These data were reported in summary form in DeHart et al () but not formally analyzed. Here, we report that the proportion of choices for larger clear‐framed money (dollars) at no delay was greater than the proportion of choices for larger fuzzy‐framed money (handfuls of quarters) at no delay (Number of choices of Small Clear Money = 2, Large Clear Money = 238; Small Fuzzy Money = 24, Large Fuzzy Money = 216; z = 4.44, p < .001).…”
Section: Discussionmentioning
confidence: 99%
“…This finding of good test–retest reliability in delay discounting is well replicated in people (e.g., Beck & Triplett, ; Black & Rosen, ; Kirby, ; Martínez‐Loredo et al, ; Matusiewicz et al, ; McCarthy et al, ; Takahashi et al, ; Weafer et al, ; Xu et al, ), and has also been found in rats (Peterson et al, ). Similarly, in alternate‐form test–retest reliability, the degree of discounting on one type of test of delay discounting is strongly related to the degree of delay discounting found with a different type of test of delay discounting in people (e.g., DeHart et al, ; Johnson & Bickel, ; Kowal et al, ; Robles & Vargas, , ; Robles‐Sotelo et al, ; Rodzon et al, ; Smith & Hantula, ) and rats (Peterson et al, ).…”
mentioning
confidence: 99%
“…The result was that participants' choices in the present experiment were well predicted by Equation 2, whereas those of McKerchar and Mazur () were not. This difference emphasizes the point that the exact structure and wording of the questions can have an important effect on decision making when participants make hypothetical choices about money (DeHart, Friedel, Frye, Galizio, & Odum, ; DeHart & Odum, ; Klapproth, ; LeBoeuf, ; Read, Frederick, Orsel, & Rahman, ).…”
Section: Discussionmentioning
confidence: 99%
“…Though there is no parametric research on the independent effects of the framing of reward magnitude on measures of delay discounting, the effects of framing have recently been investigated as a related and relevant parameter (e.g., explicit zero, Magan et al, 2008; delay phrasing, DeHart & Odum, 2015; unit framing, DeHart et al, 2018). Framing effects refer to manipulations that change the way a scenario or outcome is perceived (see Koffarnus et al, 2013 for a review).…”
mentioning
confidence: 99%
“…Framing effects refer to manipulations that change the way a scenario or outcome is perceived (see Koffarnus et al, 2013 for a review). Framing manipulations often result in different discounting patterns despite no actual change to the parameters of the scenario (e.g., DeHart & Odum, 2015) or the parameters of the outcome (e.g., DeHart et al, 2018). Regarding the framing of the scenario, Magan et al (2008) found that participants discounted less when choices were explicitly framed to emphasize the receipt of $0 for the nonpreferred outcome.…”
mentioning
confidence: 99%